Motor skill development in low-income, at-risk preschoolers: A community-based longitudinal intervention study. Issue 11 (November 2017) - Bellows, Laura L.; Davies, Patricia L.; Courtney, Jimikaye B.; Gavin, William J.; Johnson, Susan L.; Boles, Richard E.
Abstract: Objectives: This study aimed to: (1) determine the status of fundamental movement skill (FMS) performance in low-income, at-risk preschoolers; and (2) evaluate the impact of the Food Friends Get Movin ' with Mighty Moves (MM) program on improving children's FMS at two-year follow-up. Design: Longitudinal, quasi-experimental study with matched controls. Methods: The Colorado LEAP study was conducted in four Head Start/preschools (two intervention, two control) serving children aged 3–5 years. MM was delivered to the intervention group during preschool. The Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2) subtests for balance, running speed and agility, upper-limb coordination (object control (OC) skills) and strength were administered to children at baseline, post-intervention in preschool, one-year follow-up (kindergarten), and two-year follow-up (first grade). Results: Compared to the normative sample's mean, the mean scaled score for all participants at baseline was significantly lower for balance (p = 0.016) and OC skills (p < 0.001). At two-year follow-up, the means of balance for all participants and OC skills for just the control group were significantly lower than those of the normative sample (p ≤ 0.001). Hierarchical linear regression analyses revealed a significant intervention effect for OC skills with the overall model accounting for 41% of variance at two-year follow-up, F (6, 165) = 20.45, p < 0.001. No intervention effects were found for the other three BOT-2 subtests. Conclusions: Delivering the MM program in preschool confers a lasting impact on FMS, specifically OC skills, in at-risk elementary school children. Results suggest that at-risk preschoolers are already behind in FMS development and these delays will continue through first grade.